Some Determinants of Student Performance in the First College-Level Financial Accounting Course - Eskew, Robert K.; Faley, Robert H. (The Accounting Review, 1988)
[This study develops a model to explain student examination performance in the first college-level financial accounting course. A multiple regression analysis explains 54 percent of the variance in examination performance and indices of aptitude and effort account for the majority of the variance explained. However, high school and previous collegiate performance, as well as previous specific and related academic experience, each account for a significant portion of the variance in examination performance above that explained by aptitude and effort. Discrepancies between the results of the present study and other published findings are discussed.]